Controlling Decision-Making Practice in Organizations - Sutcliffe, Kathleen M.; McNamara, Gerry (Organization Science, 2001)
How are decision practices fostered in organizations and how are they linked to decision outcomes? This study addresses these questions by examining one financial institution's efforts to standardize and control decision making across geographically separated organizational units. We argue that decision-maker behavior is situated and is not simply a function of individual choice. Rather, in organizational settings decision-makers are subject to a hierarchy of influences that affect the decision processes they use and their resulting decision choices. To test our ideas, we examined 900 borrower “risk rating” decisions and found general support for our hypotheses. Decision makers were more likely to use the prescribed practice when decisions were important, when the decision target was known, and when the decision maker was located in a larger subunit. Decision makers altered their decision practices in the short term, but in the long term they appeared to partially revert to their earlier practices. Reliance on prescribed practice fostered stability in decisions, but surprisingly appeared to negatively affect future judgments. The findings indicate that organizations can change the more microaspects of decision making, but these changes may be transitory. Moreover the results suggest that decision makers may become complacent when they rely on prescribed decision practices, a tendency that can have untoward consequences for the organizations in which they are embedded.